2019
DOI: 10.33542/tjb2019-2-07
|View full text |Cite
|
Sign up to set email alerts
|

Datura innoxia Mill. (Solanaceae), a new alien species in the flora of Bosnia and Herzegovina

Abstract: Downy thorn-apple Datura innoxia Mill is native in southwest U.S.A. and Mexico. It has been recorded as a new alien species to the vascular flora of Bosnia and Herzegovina. In Bosnia and Herzegovina, D. innoxia is reported from two localities in the city of Mostar where the species has escaped cultivation and established small populations in surrounding ruderal habitats including waste land. The species is toxic to animals and humans. The paper presents a short morphological characteristic and photographs as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Datura innoxia (originally published as "inoxia" and sometimes still cited with that spelling of the species epithet, correctable under Art. 60.1 of the ICN: Turland et al, 2018) was reported in Ukraine as a cultivated ornamental plant, which until recently was planted mainly in the southern regions of the country, where it sometimes occurred as escaped (e.g., Boiko, Kolomiychuk, 2015); it is also known in many regions of Europe (e.g., Clement, 1998a;Verloove, 2006Verloove, , 2008Gudžinskas, 2017;Lakušić et al, 2017;Maslo, Šarić, 2019, and references therein). However, a closely related species, D. wrightii Regel (D. innoxia auct.…”
Section: Datura Innoxia Mill and Related Or Similar Species (Solanaceae)mentioning
confidence: 99%
“…Datura innoxia (originally published as "inoxia" and sometimes still cited with that spelling of the species epithet, correctable under Art. 60.1 of the ICN: Turland et al, 2018) was reported in Ukraine as a cultivated ornamental plant, which until recently was planted mainly in the southern regions of the country, where it sometimes occurred as escaped (e.g., Boiko, Kolomiychuk, 2015); it is also known in many regions of Europe (e.g., Clement, 1998a;Verloove, 2006Verloove, , 2008Gudžinskas, 2017;Lakušić et al, 2017;Maslo, Šarić, 2019, and references therein). However, a closely related species, D. wrightii Regel (D. innoxia auct.…”
Section: Datura Innoxia Mill and Related Or Similar Species (Solanaceae)mentioning
confidence: 99%
“…I. glandulifera Royle (= I. roylei Walp.) is an Asian ornamental plant introduced to Europe in the XIX th century from the Himalayas, becoming established as an escape from cultivation in Europe and North America (Clements et al, 2008;DAISIE, 2019;Maslo and Šaric, 2019). The species is included in the Black Book of the Flora of Central Russia (Vinogradova et al, 2010) and the Black Book of the Flora of Siberia (Ebel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…I. parviflora DC., is one of the most widespread invasive plant species in Central Europe (DAISIE, 2019;Maslo and Šaric, 2019). This species disturbs the natural vegetation composition in many European forests where it is frequently mixed with the native I. nolitangere.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are typically alternate and ovate. Flowers are zygomorphic, 7–15 mm long and white-yellow colorued with occasional thin red patterns [12]. Individual plants under favourable conditions can produce up to ten thousand seeds in the three months of the fruit growing.…”
Section: Introductionmentioning
confidence: 99%